2014
DOI: 10.1111/acer.12492
|View full text |Cite
|
Sign up to set email alerts
|

5‐HTTLPR Moderates Naltrexone and Psychosocial Treatment Responses in Heavy Drinking Men Who Have Sex with Men

Abstract: Background A functional polymorphism (5-HTTLPR) in the promoter region of the serotonin transporter gene has been widely studied as a risk factor and moderator of treatment for a variety of psychopathologic conditions. To evaluate whether 5-HTTLPR moderates the effects of treatment to reduce heavy drinking, we studied 112 high-functioning European-American men who have sex with men (MSM). Subjects participated in a randomized clinical trial of naltrexone (NTX) and cognitive behavioral therapy (CBT) for problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…In addition, for drinks consumed, this effect was also present at moderate monitoring levels. These results are consistent with prior studies finding that the 5-HTTLPR S allele is associated with negative alcohol behaviors and outcomes ( Chen et al, 2014 ; Covault et al, 2007 ; Herman et al, 2003 ), as well as those indicating that poorly monitored adolescents are more likely to use drugs ( Steinberg et al, 1994 ). Results also showed that at high levels of parental monitoring, the lower level of response to alcohol associated with the 5-HTTLPR S allele was negatively associated with alcohol-related problems.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, for drinks consumed, this effect was also present at moderate monitoring levels. These results are consistent with prior studies finding that the 5-HTTLPR S allele is associated with negative alcohol behaviors and outcomes ( Chen et al, 2014 ; Covault et al, 2007 ; Herman et al, 2003 ), as well as those indicating that poorly monitored adolescents are more likely to use drugs ( Steinberg et al, 1994 ). Results also showed that at high levels of parental monitoring, the lower level of response to alcohol associated with the 5-HTTLPR S allele was negatively associated with alcohol-related problems.…”
Section: Discussionsupporting
confidence: 91%
“…The results presented here are consistent with a substantial portion of the work involving alcohol outcomes, level of response, and variation in 5-HTTLPR. Several empirical studies and two meta-analyses point to S carriers being at increased risk for negative alcohol outcomes (e.g., Chen et al, 2014 ; Feinn et al, 2005 ; Herman et al, 2003 ; McHugh et al, 2010 ). However, other studies have reported that L carriers are at increased risk (e.g., Hu et al, 2005 ; Schuckit et al, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifteen studies evaluated the impact of interventions on alcohol outcomes (Charlebois, Plenty, Lin, Ayala, & Hecht, 2017;Chavez & Palfai, 2019;Chen et al, 2014;Croff et al, 2012;Fals-Stewart, O'Farrell, & Lam, 2009;Kahler et al, 2018;Kuerbis, Schaumberg, Davis, Hail, & Morgenstern, 2014;Millar, Wang, & Pachankis, 2016;Morgenstern et al, 2007;Morgenstern et al, 2012;Santos et al, 2016;Santos et al, 2014;Smith et al, 2017;Velasquez et al, 2009;Wray, Kahler, Simpanen, & Operario, 2019). Nearly all of these studies (n=14) were conducted in the United States.…”
Section: Alcoholmentioning
confidence: 99%
“…Of these, five were interventions to reduce alcohol consumption among SMM who engaged in heavy drinking (Chavez & Palfai, 2019;Kahler et al, 2018;Santos et al, 2016;Santos et al, 2014;Wray et al, 2019); two were designed to prevent or reduce heavy drinking among young SMM (Millar et al, 2016;Smith et al, 2017); four targeted SMM who engaged in both heavy and otherwise harmful drinking (i.e., negative consequences) (Chen et al, 2014;Morgenstern et al, 2012;Velasquez et al, 2009); and two focused on reducing alcohol consumption and preventing intoxication among bar patrons (Charlebois et al, 2017;Croff et al, 2012). (Chen et al, 2014;Kahler et al, 2018;Millar et al, 2016;Morgenstern et al, 2007;Morgenstern et al, 2012;Santos et al, 2016;Santos et al, 2014) and one on couple-level psychotherapy (Fals-Stewart et al, 2009). One study (Smith et al, 2017) evaluated a group intervention for young SMM, while another study (Charlebois et al, 2017) adopted a multi-pronged approach that included structural (i.e., physical environment), environmental (e.g., in-bar media campaign), and individual elements in a venue-based (gay bar) setting.…”
Section: Alcoholmentioning
confidence: 99%